Comprehensive use of Hip Joint in Gender Identification Using 3-Dimension Data - Sajid Ali; Zhou Mingquan; Wu Zhongke; Abdul Razzaq; Mohamed Hamada; Hafeez Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Way of walking is a spatio-temporal phenomenon that typiﬁes the motion characteristics of human. In this paper, we propose a human gender identification method based on the outdoor surveillance of human gait using statistical techniques and geometrical function applied to three-dimensional (3D) joint movement data. The statistical techniques are used to define the features of the joint of the human gait, and the geometrical function applied for gender recognition. Our proposed scheme is based on extraction of the concern joint (hip joint) data that provides plentiful information for gender recognition. Here the rotation angle data of a hip joint were computed from the Biovision Hierarchical data (BVH file). The use of BVH file for human gender recognition is a novel feature of our work. The results indicated that the proposed approach is highly reliable for gender recognition. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2274